Religiusitas dan Kewirausahaan; Faktor Kritis dalam Mencapai Kinerja Bisnis pada UKM di Kabupaten Malang - Rita Indah Mustikowati; Sri Wilujeng (Jurnal Studi Manajemen dan Bisnis, 2018)
Religiosity are extremely abstract and subjective.From this perspective, the extent to which the level of religiosity that is owned by a person will affect the achievement of the firm performance, including SME’s. Thus, the purpose of this research is to examine some of the factors that affect the achievement of the performance based on the perspective of religiosity.The research population is all of SME’s In Malang, with a total sample of 100 SMEs. Sampling method that used to collecting data is probability sampling method, with Proportional Random Sampling techniques. Methods of data analysis used is Multiple Regression. Based on the results of hypothesis testing showed that all the factors that exist on the concept of religiosity, including honesty, ethics, moral and mutual value the influence on business performance improvements. Thus, in order to the business performance increased, the entrepreneurs SMEs in Malang should increase the level of religiosity.